CW-Laser-Induced Solid-State Reactions in Mixed Micron-Sized Particles of Silicon Monoxide and Titanium Monoxide: Nano-Structured Composite with Visible Light Absorption - Křenek, Tomáš; Tesař, Jiří; Kupčík, Jaroslav; Netrvalová, Marie; Pola, Michal; Jandová, Věra; Pokorná, Dana; Cuřínová, Petra; Bezdička, Petr; Pola, Josef (Journal of inorganic and organometallic polymers and materials, 2017)
Silica–titania mixed oxides and composites have been broadly examined for their physical and catalytic properties, but titanium monoxide–silicon monoxide counterparts have yet drawn very little attention. Here we report that laser-induced processing of mixed silicon and titanium monoxides results in reactions yielding a nanostructured Ti/Si/O composite absorbing visible light. Changes in the composition of intimately mixed μm-sized particles of silicon monoxide (SiO) and titanium monoxide (TiO) induced by scanning of a cw CO 2 laser beam along the TiO–SiO pellet surface were examined by FTIR and Raman spectroscopy, X-ray diffraction and electron microscopy. They are shown to consist in the evolution of TiO 2 (rutile and anatase), titanium suboxides (Ti 4.5 O 5 , Ti 2 O 3 ), silica and amorphous binary SiO x , TiO x and ternary Si x Ti y O z nano-phases which contain less or more O than SiO and TiO monoxides. These products are ascribed to concurrent silicothermal reduction of TiO and O-transfer between SiO and TiO due to interdiffusion of Si- and Ti-based species. These reactions taking place under transient localized heating are not inhibited by passivation shells around SiO and TiO particles. The laser-produced Ti/Si/O composite shows absorption band at 425 nm tailing up to 1100 nm. Its solar-light photocatalytic activity in decolorization of Methylene Blue is compared to that of the unheated SiO and TiO powders absorbing only in UV region.